REPRESENTASI BUDAYA BATAK MANDAILING PADA DESAIN PRODUKSI FILM PENDEK FIKSI “BABIAT SITELPANG”: REPRESENTATION OF MANDAILING BATAK CULTURE IN THE PRODUCTION DESIGN OF THE SHORT FICTION FILM "BABIAT SITELPANG" - Abil, Abdillah Fadlan; Salsa Solli Nafsika , Salsa Solli Nafsika; Hery Supiarza , Hery Supiarza (Arty: Jurnal Seni Rupa, 2024)
Film is an audio-visual mass media that can be used for a variety of messages to be conveyed in the movie. The type of narrative film is one of the strong media to explore issues that occur in society. Issues that are then visualized in the form of images and sounds are arranged in a representative fictional storyline. This research uses descriptive qualitative method in determining mise-en-scene in the movie to discuss the elements seen in the frame. In the film "Babiat Sitelpang" by director Asrizal Hasibuan, a UPI Film and Television student, Mandailing Batak culture is packaged in production design or artistic arrangement in the film. Through several approaches, the Batak Mandailing culture presented becomes distinctive in the movie, starting from the language used in Mandailing Batak, the character's residence is the same as in Batak, the character's surroundings, and the character's harsh lifestyle. This research shows that the strength of a movie is not built on the plot alone but the artistic elements of a movie.